Analysis of Performance of Farmer Producer Organizations in Kalaburagi District of Karnataka - Pooja; H.K. Pankaja; B. Krishnamurthy (Journal of Agricultural Extension Management, 2022)
Small-holder farmers, who account for 82 per cent of all farmers in India, are critical to the country’s agriculture and rural economy. Farmers must be mobilized into a Government of India effort, such as a collective, Farmer Producer Organizations for collective action. To maximize the collective bargaining power of producer organizations, it is necessary to work not only with small and marginal farmers and their institutions but also with FPOs and their promoting organizations to create an enabling environment for smooth functioning producer organizations and to assist them in overcoming obstacles that they face on a daily basis. The present study was conducted during 2020-2021 in Kalaburagi district of Karnataka state. The objective was to study the profile characteristics of FPO members and to analyze the performance of FPOs. The study revealed that most of the FPOs (47.20%) were having an average level of performance, followed by better (27.20%) and poor (25.60%) levels of performance. There has been a substantial increase in the number of FPOs in India, the ecosystem needs to be more developed in each state in support of these growing FPOs.